Asset and inventory management system for ESPEK, RISDA, Kuala Lumpur / Eyanto Dsyam Asmady Abas - Abas, Eyanto Dsyam Asmady (Faculty of Computer Science and Mathematics, 1999)
The development of Asset and Inventory Management System is proposed by Estet Pekebun Kecil SDN. BHD. (ESPEK). ESPEK is one of the subsidiary companies of RISDA. The main objective of this system is to help ESPEK in keeping track of assets and inventories purchased. The classification of an item whether it falls under asset or inventory is based on the price of the item. If the price of the item is equal or above RM 5000 then it will be considered as asset, otherwise it will be considered as inventory. The importance of keeping track is to enhance the administrators' task in monitoring the condition and location of a particular asset or inventory. The condition monitoring process of an asset covers only the physical structure while the condition monitoring process of an inventory covers the physical structure within a specified time range starting from the date of purchase until the date of expire. The location monitoring process is almost similar for both asset and inventory except that inventory items are usually transferred from one location to another. The method implemented here is by storing the information of an asset or inventory in a database and designing an interface to have access to the database. In this project, the development of database structure is using Microsoft''^'*' Access 97 while the interface is developed using Microsoft^^ Visual Basic 6.0 (Professional Edition).